Sea level changes due to climate change – facts and fiction - Saha, SK; Monsur, Md Hussain (Journal of Nepal Geological Society, 2008)
Climate is increasingly warmer almost every day, a general paradox to the commons. This is what has become known as Global Warming. The driving idea is that there is a linear relationship between CO2 increase in the atmosphere and global temperature. The fact, however, is that temperature has constantly gone up and down. From 1850 to 1970, an almost linear relationship with solar variability; not CO2 was observed. For the last 30 years, the data sets are so contaminated by personal interpretations and personal choices that it is almost impossible to sort up the confusion in reliable and unreliable data. Most remarkable in the record of climatic changes during the last 600 years are the cold periods around 1450, 1690 and 1815 and their correlation with periods of Solar Minima (the Spörer, Maunder and Dalton Solar Minima). The driving cyclic solar forces can easily be extrapolated into the future. This would call for a new cold period or “Little Ice Age” to occur at around 2040-2050. Still, we hear nothing about this. It is as if IPCC and the Kyoto Protocol enthusiasts want to “switch off the Sun itself”. In the global warming concept, it has been constantly claimed that there will be a causal rise in sea level; a rise that already is in the accelerating mode, in the near future to cause extensive and disastrous flooding of low-lying coastal areas and islands. Is this facts or fiction? It is true that we are flooded by this information. The recording and understanding of past changes in sea level, and its relation to other changes (climate, glacial volume, gravity potential variations, rotational changes, ocean current variability, evaporation/precipitation changes, etc.) is the key to sound estimates of future changes in sea level. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.30